2020
DOI: 10.1016/j.cej.2020.124470
|View full text |Cite
|
Sign up to set email alerts
|

As(III) adsorption on Fe-Mn binary oxides: Are Fe and Mn oxides synergistic or antagonistic for arsenic removal?

Abstract: Fe-Mn binary oxides are ubiquitous in the natural environment and have attracted increasing interest due to their high removal capacity for As(III), as well as their important role in the natural cycling of arsenic. Although numerous studies have characterized the respective roles of Fe and Mn oxides in As(III) removal, the relationship between different Fe-Mn binary oxides for As(III) removal has not been fully explored. In this study, three Fe-Mn binary oxides containing either ferrihydrite, hematite or goet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(31 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Considering the experimental conditions and the adsorption process parameters such as pH solution, sorbent mass, initial concentration of pollutant material, and the experiment duration, the adsorption capacity of As(III) ions by iron oxide or iron oxide composites was reported between 8 and 66.53 mg/g [ 11 , 45 , 46 ]. Nonetheless, during the years, extensive research has been conducted with the sole purpose of improving the properties of adsorbents [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Moreover, in their recent studies, Otero-González et al [ 13 ] reported that the estimated maximum adsorption values (q max ) values obtained in the case of As(III) retention on novel nanostructured iron oxide cryogels were 625 and 588 mg As(III) per g of Fe for the IO gel and the IO/AAm/MBAA cryogel, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the experimental conditions and the adsorption process parameters such as pH solution, sorbent mass, initial concentration of pollutant material, and the experiment duration, the adsorption capacity of As(III) ions by iron oxide or iron oxide composites was reported between 8 and 66.53 mg/g [ 11 , 45 , 46 ]. Nonetheless, during the years, extensive research has been conducted with the sole purpose of improving the properties of adsorbents [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Moreover, in their recent studies, Otero-González et al [ 13 ] reported that the estimated maximum adsorption values (q max ) values obtained in the case of As(III) retention on novel nanostructured iron oxide cryogels were 625 and 588 mg As(III) per g of Fe for the IO gel and the IO/AAm/MBAA cryogel, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption isotherms for the arsenic removal by IO-CTAB nanoparticles were obtained by mixing solutions containing different concentrations of As(III) with 0.2 g of IO-CTAB nanoparticles until thermodynamic equilibrium at ambient temperature (T = 25 • C) was achieved. Previously reported studies emphasized that the thermodynamic equilibrium at ambient temperature can be achieved in less than 24 h [13][14][15][16][17][18][19][20][21].…”
Section: Adsorption Kinetics and Isothermsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these methods, adsorption has attracted more attention due to its ease of operation, low cost, sustainability, efficiency, low waste generation and low energy requirement (Weerasundara et al 2021;Amen et al 2020). Many different natural and synthetic adsorbents have been tried to remove arsenic from water including industrial and agricultural wastes (Mohan and Pittman Jr 2007), Fe-Mn binary oxides (Zheng et al 2020), fly ash (Ochedi et al 2020), chitosan (Kloster et al 2020), activated carbon (Hashim et al 2019), and activated alumina (Tripathy and Raichur 2008). In recent years, zeolites have been used to remove many pollutants such as arsenic from water and wastewater due to their high surface area, easy availability, and low cost (Figueiredo and Quintelas 2014;Asere et al 2019).…”
Section: Introductionmentioning
confidence: 99%